A novel group parenting intervention to reduce emotional and behavioural difficulties in young autistic children: protocol for the Autism Spectrum Treatment and Resilience pilot randomised controlled trial. Issue 6 (27th June 2019) - Palmer, Melanie; Tarver, Joanne; Paris Perez, Juan; Cawthorne, Thomas; Romeo, Renee; Stringer, Dominic; Hallett, Victoria; Mueller, Joanne; Breese, Lauren; Hollett, Megan; Beresford, Bryony; Knapp, Martin; et al.
Abstract : Introduction: The majority of young autistic children display impairing emotional and behavioural difficulties that contribute to family stress. There is some evidence that behavioural parenting interventions are effective for reducing behavioural difficulties in autistic children, with less evidence assessing change in emotional difficulties. Previous trials have tended to use unblinded parent-report measures as primary outcomes and many do not employ an active control, limiting the conclusions that can be drawn. Methods and analysis: The Autism Spectrum Treatment and Resilience study is a pilot randomised controlled trial (RCT) testing the specific effect of a 12-week group parenting intervention (Predictive Parenting) on primary and secondary outcomes, in comparison to an attention control condition consisting of psychoeducation parent groups. Following a feasibility study to test research procedures and the interventions, the pilot RCT participants include 60 parents of autistic children aged 4–8 years who are randomised to Predictive Parenting versus the attention control. Measures are administered at baseline and post intervention to assess group differences in child and parent outcomes, costs and service use and adverse events. The primary outcome is an objective measure of child behaviours that challenge during interactions with their parent and a researcher. The trial aims to provide data on recruitment, retention, completion of measures and acceptability of the intervention and research protocol, in addition to providing a preliminary indication of potential efficacy and establishing an effect size that could be used to power a larger-scale efficacy trial. We will also provide preliminary estimates of the cost-effectiveness of the interventions. Ethics and dissemination: Ethical approval was granted from NHS Camden and Kings Cross Research Ethics Committee (ref: 16/LO/1769) along with NHS R&D approval from South London and Maudsley, Guy's and St Thomas', and Croydon Health Services NHS Trusts. The findings will be disseminated through publication in peer-reviewed journals and presentations at conferences. Trial registration number: ISRCTN91411078